The Influence of Product Quality, Product Innovation, and Brand Image on Consumer Purchasing Decisions for the Eiger Brand in Denpasar City - I Nyoman Adi Prasyatiya; Bayu Pasupati; Ida Ayu Putu Santi Purnamawati (Journal of Governance, Taxation and Auditing, 2026)
This study aims to examine how product quality, innovation, and brand perception influence consumer purchasing choices for the Eiger brand in Denpasar City. A quantitative methodology was employed through a survey conducted with 98 participants selected using a purposive sampling method. Data were collected using a Likert-scale questionnaire and evaluated using various statistical measures such as reliability, classical assumption assessment, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²). The findings are expected to demonstrate that product quality, product innovation, and brand image can influence consumer purchasing behavior, both individually and collectively, serving as the basis for strategies to increase a company's market competitiveness.